Experimental investigation on impacts of tsunami-induced forces on coastal structures / Sadia Rahman - Sadia, Rahman (2014)
The recent tsunamis have showed their terrifying impacts and disastrous destructions to the coastal region. Near shore, infrastructure systems comprising buildings, bridges, highways, other road facilities, utilities etc. are critically at risk of substantial damages by the exerted tsunami forces. Tsunamis are long oceanic waves caused mainly due to the rapid displacement of water induced by the earthquake in the ocean floor. Waves disseminate away from their generating source at significant speed and propagate toward the shore. Upon approaching the shallow water near the coast, their speed and wavelengths reduce; however, their wave height increases significantly. While propagating along the shore, waves contain tremendous energy and hit the nearby coastal zones violently. Recorded videos from the historical tsunamis showed that the tsunami waves propagated as hydraulic bores. Dam-break mechanism is the most studied method of producing waves that transmit like hydraulic bores. In this study, a comprehensive research was performed to examine the impact of tsunami-induced forces on two different types of coastal structures (bridge and building). Forces and wave heights were measured using the load cell and the wave probe, respectively. In the case with bridge structures, both broken and unbroken waves were simulated where the measured horizontal forces were larger for the broken waves. When the girder was located in a higher position, measured forces were larger. This fact indicated that the bridges with higher girder height are more vulnerable to the tsunami hazard. Experiments were also performed with about 16 % perforations in the girder and approximately 10 % to 18 % of force reductions were achieved. Results revealed that perforations in the girder are effective in reducing tsunami forces. For the case with square building model, the initial impact forces were larger than the hydrodynamic forces with larger reservoir depths. The hydrodynamic forces exceeded the impact forces at smaller reservoir depth. The average CD (drag coefficient) value was 1.31 which was very close to FEMA 55 suggested values. The advantages of opening in the building against tsunami forces were evaluated where approximately 10 % to 65 % of forces were reduced due to the presence of the opening. Seawall with enough height and positioned closer to the building model provided better performance by obstructing the incoming waves. Another research was performed with perforated seawall. As the amount of force reduction attained by the perforated seawall was almost similar to the solid seawall, this study proposed the use of the perforated wall instead of a solid wall. Perforated wall allows easy receding of water to go back to sea, whereas solid wall traps the coming water behind and thus, creating additional forces on the building. Less construction cost of the perforated wall makes it more attractive than the solid wall. The effects of the upstream barriers on the building model were assessed by placing different size barriers in different locations in front of the model. Thinner barrier placed closer to the model provided more protection against the tsunami.